Pattern of Microbes Associate to Acute Appendicitis at Liaquat University Hospital (Medical Forum Monthly, 2024)
Objective: To identify the most common of causative microbes associate to acute appendicitis and choice of different antibiotics according to sensitivity.Study Design: Observational and Prospective StudyPlace and Duration of Study: This was carried out in the Department of Surgery, Liaquat University Hospital, Hyderabad from January 2009 to January 2010.Materials and Methods: In this study patients various cultures obtained at the time of appendectomy was sent under sterile conditions for isolation of organisms and their sensitivity were sent to university hospital. The condition of the appendix regarding catarrhal inflammation, perforation and gangrene were noted on the preformed. Cultures were sent from the appendix wall and peri appendix peritoneal fluid for aerobics and anaerobic cultures.Results: Total number of 100 culture reports of the patients who underwent open appendectomy was enrolled in this study irrespective of sex. The Pipracillin + Amikacin was the most effective (41.8%, n = 55) antibiotic followed by Ceftazidime + Amikacin, the second commonest effective antibiotic in 17 patients (30.9%).Conclusion: We conclude that the most common isolated organisms of the aerobes were found sensitive against cephalosporins. Pipracillin tazobactum and Quinolones are the most sensitive antimicrobial to most of the pathogens isolated in our study.